Penerapan Sistem Informasi Manajemen Pendidikan dalam Pengelolaan Tracer Study di SMK Mulia Bakti Purwokerto - Pangestika, Meti Muji; Mahfud; Nurfuadi (Al-Wasathiyah: Journal of Islamic Studies, 2024)
The implementation of the Education Management Information System (SIMP) at Mulia Bakti Purwokerto Vocational School aims to increase the efficiency and effectiveness of data management and administrative processes, especially in managing tracer studies. Tracer study is an important activity carried out to collect data regarding the success of alumni in entering the world of work and the relevance of the curriculum to industry needs. This research uses a qualitative approach, with data collection methods through interviews, observation and literature study. The research results show that SIMP has succeeded in increasing the accuracy, completeness and speed of alumni data collection. Data collected through SIMP allows a more comprehensive analysis of alumni success rates, with a success percentage reaching 90% by 2024. However, there are still several obstacles, such as a lack of alumni awareness about the importance of filling out tracer study forms, limited internet access, and a lack of training for teachers and staff. Recommendations to overcome this obstacle include improving communication and outreach to alumni, providing better internet access, and training for teachers and staff. Overall, the application of SIMP in managing tracer studies at Mulia Bakti Purwokerto Vocational School not only provides useful data for evaluating educational programs, but also contributes to bridging the gap between education and industry, thereby improving the quality of vocational education and preparing graduates who are competitive in the job market.